The pattern of p53 gene mutations on oral squamous cell carcinoma - Peter Agus (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Oral squamous cell carcinoma (OSCC) is the result of accumulation genetic lesion and caused by specific mutation in specific key regulation genes. p53 gene is key target specific regulatory genes which function as negative regulators in cell cycle control. The highest mutation rates found in human cancers and the etiology in high risk populations and the pattern of molecular pathogenesis mechanism involved in the OSCC remain unclear. The purpose of this study was to determine the presence of alteration or mutation of p53 gene and to associate these mutations histopathological status of the patients such as well differentiated and poorly differentiated in OSCC in order to elucidate the molecular pathogenesis mechanism of OSCC based on the pattern of p53 gene. Using 40 untreated well and poorly differentiated OSCC biopsy samples and 16 normal patients were analyzed for the presence of mutation in the conserved region of the p53 gene exons 5 and or 7 by PCR-SSCP mutational analysis for p53 gene showed 70% of total samples : exon 5: 27.5% with heterozygous mutation 81.8%, exon 7: 55% with heterozygous mutation 100%. The incidence of p53 mutation was not significantly associated with well and poorly differentiated OSCC with the exception in exon 5 of p53 gene (p = 0.013) using contingency coefficient. This study concludes that mutation of p53 gene especially in exon 7 may not indirectly play in the progressivity of OSCC with the exception of mutation in exon 5 of p53 which indicates the essential role in the progressivity of OSCC.